Integrating Cybersecurity into Data Management: A Unified Framework for Office Data Security (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The accelerated rate of digitization within the context of the office environment has seen organizational dependence on digital information systems escalate concurrently with an increased threat profile for cybersecurity breaches. This current study seeks to investigate the integration of active cybersecurity controls within the context of organizational data management to improve the security posture for data confidentiality, integrity, and availability. To this end, a mixed-methods research design was utilized to investigate this problem, incorporating a systematic review of existing literature and a quantitative survey of 150 mid- to large-scale organizations. The results highlight a significant disparity between the implementation of individual cybersecurity tools and the development of an overarching cybersecurity framework. The results demonstrate that organizations that implement an integrated data management system, incorporating end-to-end encryption, multi-factor authentication, rigorous administrative controls, cybersecurity training for staff, and effective data governance practices, are significantly less likely to experience data breaches when compared to organizations that implement a disjointed approach to cybersecurity. Additionally, this study recognizes organizational security awareness culture as a key influencer on cybersecurity posture, as employee awareness has a direct influence on the efficacy of cybersecurity controls and the mitigation of cybersecurity threats. As such, this study proposes a Unified Office Data Security Management (ODSM) framework that incorporates a holistic approach to cybersecurity controls to protect organizational data. The proposed framework provides a guide for organizations to improve cybersecurity governance, organizational resilience, and sustainability.